Detection in neuronal communications with finite channel state - Amiri, Abolfazl; Salehkalaibar, Sadaf; Maham, Behrouz (My University, 2017)
Abstract Nano-networks are the key factors in developing future nano-machines. The use of molecules to transmit information in such networks is the subject of molecular communications. The future of the nano-networks depends on the development of the molecular communications. Neuro-synaptic communication, which models the data transmission in the body nervous system, is an important example of molecular communication. In this paper, we introduce a comprehensive channel model for the neuro-synaptic communication channel. Our model incorporates the effect of different channel states and spike rates that exist in the body nervous system. We propose a finite state Markov channel scheme for the communication system. This scheme has a two dimensional state space according to the neural firing rate and the number of available carrier resources. Next, we suggest an M-ary signaling scheme for the synaptic area that models the synaptic multi-site activity. In this activity, several neuronal endpoints participate in the neurotransmitter release process. Moreover, we obtain a closed-form solution for the detector at the destination neuron. Finally, we evaluate the decision rules in the detector with simulations.
Keywords: Molecular communications; Neuro-synaptic communications; Finite state Markov channel; MAP detector